نموذج مقترح لتصميم نظم التعليم الالكتروني التفاعلية - طه ياسين اسماعيل; محمد عمر حمودي (PROSPECTIVE RESEARCHES, 2023)
In recent years, the uses of E-learning systems have increased. Due to this reason there is a need to develop a general principles and guidelines for the analysis and design of these systems, which can guide the developers and content designers to standard methods for design, in addition to guiding the lecturers on how to design and manage their tutorials. Currently there are many of these systems, but they are disparate in their quality. In most of these systems there is a gap between the needs of system developers, lecturers and students. In this research we attempt to develop an e-learning system that is trying to bridge this gap. It lays lecturing plans for each semester, course, registration and examination. The content analysis and design has been carried out by a proposed methodology. The system depends on of the approach used by Iraqi universities.